Screening and Identification of Chromium Resistant Bacteria from Poultry Excreta - Khan, Md Abu Sayem; Badhon, Md Muzahidul Islam; Rivu, Supantha; Rahman, Sabita Rezwana (Bangladesh Journal of Microbiology, 2024)
The occurrence of heavy metal-resistant bacteria in the environment acts as an indicator of heavy metal pollution. The impact of heavy metal contamination in co-selection and proliferation of antimicrobial[1]resistant bacteria is well-documented in existing literature. The present study aims to determine the occurrence of chromium-resistant bacteria (CRB) in poultry feces and to characterize their antimicrobial resistance and biofilm formation ability. 28 CRBs were isolated by inoculating samples on chromium-amended media. 6 of 28 isolates were resistant to a maximum of 1000 ppm chromium. Isolated CRBs also showed varying degrees of resistance to other heavy metals, including Cd, Ni, and Hg. Biofilm formation was observed in 67.8% isolates, of which 60.7% and 7.1% were weak and moderate biofilm former, respectively. All the isolates exhibited sensitivity to Gentamicin, Chloramphenicol, Imipenem, and Amikacin. Only one isolate was multi-drug resistant. In addition, all the isolates possessed chromate reductase gene that confirmed their chromium-reducing activity. Two isolates were identified as Bacillus altituidinis and Brevibcillus parabrevis on the basis of 16s rRNA analysis. Further estimation of chromium-reduction capacity and whole genome analysis will reveal their bioremediation potential. Bangladesh J Microbiol, Volume 40, Number 1, June 2023, pp 1-6